The neuropeptide CCHamide2 regulates diuresis in the Chagas disease vector Rhodnius prolixus - Capriotti, Natalia (2019)
Given that hematophagous insects ingest large quantities of blood in a single meal, they must undergo a rapid post-prandial diuresis in order to maintain homeostasis. In the kissing bug Rhodnius prolixus (Hemiptera: Reduviidae), the coordinated activity of the Malpighian tubules and anterior midgut maintains water and ion balance during the post-prandial diuresis. Three to four hours after the meal the diuretic process finishes, and the animal enters an antidiuretic state to ensure water conservation until the next blood intake. The diuretic and antidiuretic processes are tightly regulated by serotonin and neuropeptides in this insect. In the present work, we report that the neuropeptide precursor CCHamide 2 is involved in the regulation of the post-prandial diuresis in the kissing bug R. prolixus. Our results suggest a dual effect of RhoprCCHamide2 peptide, enhancing the serotonin-induced secretion by Malpighian tubules, and inhibiting serotonin-induced absorption across the anterior midgut. To our knowledge, this is the first report of a hormone presenting opposite effects in the two osmoregulatory organs (i.e. midgut and Malpighian tubules) in insects, probably reflecting the importance of a well-tuned diuretic process in hematophagous insects during different moments after the blood meal.